Pattern of Menarche Age in Two Generations Among Female Medical Students in Faculty of Medicine Sriwijaya University - Nabila Rizki Sakinah; Ziske Maritska; Lusia` Hayati (Fakultas Kedokteran Universitas Sriwijaya, 2021)
In life, women go through many significant events in their growth and body development, one of which is experiencing their first menstruation that commonly occurs during adolescence. In sexual development, the first episode of the first bloodstream is called menarche. The age of menarche is different for each individual, and on average happens in the age range of 11-15 years old. Like many other complex traits, menarcheal age is influenced by many factors, such as genetic and environmental. This study is done to know more about the age distribution of mothers and their daughters to observe the inheriting trend of menarcheal age. This is a descriptive study using 154 samples collected from Faculty of Medicine Universitas Sriwijaya University students batch 2017 that meet the inclusion criteria. Based on the results of research conducted on female students of the Doctor Program Faculty of Medicine Universitas Sriwijaya batch 2017, there is a similarity of distribution in the age of menarche experienced by mothers and their children. Among respondents, the highest age of distribution for female students are between 12 to 14 years old which is 66,9%. For mothers, the age of menarche is the highest between the age of 12 to 14 years old, namely 77,3%. Female students' BMI has the highest distribution of data in normal scores, which is 70,8%. The distribution of menarcheal age on female students Doctor Program Faculty of Medicine Sriwijaya University and mothers have the biggest number in between the age of 12 and 14.